The Relationship of Risk Factors to the Incidence of Tuberculosis in the Working Area of the Karangpenang Public Health Center, Sampang Regency - Dimas Bangkit Irawan (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: WHO reported that the estimated total number of people diagnosed with TB in 2021 globally was 10.6 million cases, an increase of about 600,000 cases from 2021 which was estimated at 10 million TB cases. The incidence of TB cases in Indonesia is 354 per 100,000 population. The target of finding cases and suspected cases of pulmonary tuberculosis at the Karangpenang Public Health Center in 2022 is the first rank of the most out of all Public Health Centers in the working area of the Sampang District Health Office. Objective: To determine the risk factors associated with the incidence of pulmonary TB disease in the working area of the Karangpenang Public Health Center.  Method: This type of research is an analytical survey with a case control study design. The total sample was 64 with details of 32 cases and 32 controls. Results and Discussion:  Based on analysis with chi-square test, it was concluded that there was a significant relationship between nutritional status and the incidence of pulmonary TB (p = 0.002<0.05), there was a statistically significant relationship between the history of DM disease and the incidence of pulmonary TB (p = 0.018 <0.05), there was a statistically significant relationship between smoking history and the incidence of pulmonary TB (p = 0.024<0.05) in the working area of the Karangpenang Public Health Center.  Conclusions: Nutritional status, history of diabetes, history of smoking and other risk factors associated with the incidence of tuberculosis